Effects of Gypsum and Zeolite on Nutrient Uptake and Shallot (Allium ascalonium L.) Growth on Irrigated Saline Entisol - Rahayu Rahayu; Jauhari Syamsiyah; Livia Dewi (JOURNAL OF TROPICAL SOILS, 2019)
Entisols is soil that newly formed and has diverse fertility, and potential for shallot cultivation.. The center of shallot production is mostly carried out in coastal areas which have a limiting factor high soil salinity. High salinity will cause nutrient uptake and plant growth disrupted. Soil amendments such as zeolite and gypsum potential option to overcome tha impact of high salinity. This study was completely randomized design (CRD) two factors, shallot cultivar (Brebes cultivar = V1, Purbalingga cultivar = V2, Pemalang cultivar = V3), and soil amendment (gypsum = G, zeolite = Z, without amendments= K. Each pot countaned of 15 kg of entisols and irrigated by 1 liter saline water of 2 mS / cm every day. Results shallot that amendment application can significantly improve pH, EC, SAR. Application of gypsum (25 Mg ha-1) and zeolite (15 Mg ha-1) showed the higher effect on purbalingga cultivars (V2). Interaction amendments and cultivars did not significantly affect on plant height and diameter of the bulbs. Gypsum 25 Mg ha-1 (G) significantly increased wet weight and fresh weight of bulb in purbalingga cultivars.